Pengaruh Panjang Jaring Pukat Cincin Terhadap Hasil Tangkapan Nelayan di Perairan Utara Aceh - Makwiyah A. Chaliluddin; Alvi Rahmah; Fauzi Syahputra; Muqtamar Effendi; Nasruddin M. Jalil; Fitri Indah Yani (JURNAL GALUNG TROPIKA, 2021)
This research was conducted for one year, which was divided into 4 quarters. The average of each quarter was used as a replication. This study aimed to determine the composition of purse seine catch and the effect of the length of the purse seine on the catch of fishers in the waters of northern Aceh. The sample in this research is purse seine which has a length of 800 m, 900 m, 1000 m, and 1200 m. The composition of the fishermen's catch during the study was skipjack, mackerel, lemuru, and layang. The test results using ANOVA in the treatment of the ring seine length group obtained the value of F-count is 40.275 or significant (0.000). The ANOVA test on replications obtained a value of F-count is 1.623 or a significance value (0.082), meaning that the length of the 1200 meter seine had a significant effect on the fishermen's catch, while the number of replications, namely the observation time during the study year, had no significant effect on the fishermen's catch.